2023
DOI: 10.1371/journal.pone.0292651
|View full text |Cite
|
Sign up to set email alerts
|

How do public services supply, livelihood capital, and livelihood strategies affect subjective poverty?

Yuanquan Lu,
Li Chen,
Yuan Meng

Abstract: Poverty is not only an economic problem but also a social problem, and there are certain limitations of objective poverty based on the population’s income. It does not reflect the residents’ true feelings regarding education opportunities, pension and medical security, and participation in decision-making. Researchers have studied it intensively in different objective dimensions of Chinese poverty, and little attention has been paid to subjective poverty. This study analyzes how public services supply, livelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…This accomplishment has not only had a profound domestic impact but also made a significant global contribution to the battle against poverty. Recent data from China revealed that by the conclusion of 2020, an impressive 98.99 million individuals residing in rural regions were successfully lifted out of poverty 6 9 . This milestone signifies the fulfillment of the objective of eliminating poverty and establishing a comprehensive and prosperous society for the new era.…”
Section: Introductionmentioning
confidence: 99%
“…This accomplishment has not only had a profound domestic impact but also made a significant global contribution to the battle against poverty. Recent data from China revealed that by the conclusion of 2020, an impressive 98.99 million individuals residing in rural regions were successfully lifted out of poverty 6 9 . This milestone signifies the fulfillment of the objective of eliminating poverty and establishing a comprehensive and prosperous society for the new era.…”
Section: Introductionmentioning
confidence: 99%